Thermosensitive In Situ Ophthalmic Gel for Effective Local Delivery and Antifungal Activity of Ketoconazole Nanoparticles - Chutima Chaiwut; Sarin Tadtong; Puriputt Akachaipaibul; Jutamas Jiaranaikulwanitch; Sudarshan Singh; Siriporn Okonogi; Dwi Marlina Syukri; Chuda Chittasupho (Gels)
Fungal keratitis is a severe ocular infection caused by pathogenic fungi, leading to potential vision loss if untreated. Current antifungal treatments face limitations such as low solubility, poor corneal penetration, and limited therapeutic options. This study aimed to develop a thermosensitive in situ gel incorporating ketoconazole nanoparticles (NPs) to enhance drug solubility, stability, and antifungal activity. Ketoconazole NPs were prepared using the solvent displacement method, achieving a particle size of 198.25 ± 27.51 nm, encapsulation efficiency of 94.08 ± 0.51%, polydispersity index of 0.42 ± 0.08, and a positive zeta potential value of +10.08 ± 0.19 mV. The NPs exhibited sustained zero-order release kinetics. The optimized NPs were incorporated into a poloxamer-based in situ gel, demonstrating a gelation temperature of 34.67 ± 0.58 °C and the shortest gelation time. The formulation provided a 5-fold increase in solubility and a 10-fold improvement in drug release compared to pure ketoconazole. Stability studies confirmed the gel retained its physicochemical and rheological properties for three months under various storage conditions. The in situ gel showed sustained release, effective antifungal activity against Malassezia furfur, and good tolerability, suggesting it as a promising alternative for treating fungal keratitis with improved bioavailability and patient compliance.